Optimizing production potential in bovines by managing ovarian rebound - K, Singh; N, Biswas; S, Kumar; S, Parmar; N, Srivastava (Indian Farming, 2024)
Dairy farming focuses on successful cattle reproduction, with the postpartum period playing a crucial role in achieving normal fertility and calving intervals. The ovarian activity in postpartum cows is dependent on a functional hypothalamic-pituitary interaction. Pregnancy restricts follicular development in cows immediately after calving. Since ovarian alterations occur every 4 days in dairy cows, it is imperative that restoration of postpartum ovarian cyclicity (ovarian rebound) is achieved as quickly as possible for optimum breeding efficiency. Ovarian rebound is a crucial physiological process, and it plays an important role in recovery of cyclicity in cows.There are several managemental and clinical approaches to address the several facets of postpartum complications that may affect the process of resumption of ovarian activity. The proper knowledge and their application may be helpful for the farmers to enhance their profitability.